Scholarly development for primary care residents. (22nd January 2016) - Anandarajah, Gowri; Gupta, Priya; Jain, Nupur; El Rayess, Fadya; Goldman, Roberta
Summary: Background: Development, evaluation and dissemination of primary care innovations are essential for the future of health care; however, primary care physicians including family physician, lag behind hospital‐based physicians in research productivity. Family medicine residencies struggle to implement scholarly skills training programmes for busy family physicians. The Primary Care Scholarly Development Program (PC‐SDP) aimed to empower residents to incorporate innovation with scholarship into future practice, by facilitating successful resident scholarly projects and reducing perceived barriers. Methods: Educational intervention. The required PC‐SDP was piloted through a family medicine residency programme in the USA. Key elements included: rigorous but achievable requirements; emphasis on Boyer's scholarship of application, teaching and discovery; resident engagement, through the support of their 'professional passions'; basic research training; multilevel mentoring; and modest curriculum time.Evaluation. A mixed‐methods longitudinal evaluation included: (1) a qualitative study of intervention class; (2) assessing the scholarly output of the intervention class versus the comparison class; and (3) a follow‐up survey of both groups after 3 or 4 years. Results: Data were analysed from all 25 residents in the classes of 2008 and 2009 (12 intervention; 13 comparison). Qualitative interviews of residents from the intervention group revealed that their initial feelings of trepidation about scholarly work gave way to feelings of accomplishment and confidence in their ability to integrate scholarship into busy careers. Residents in the intervention group had a greater volume of scholarly output at graduation, and follow‐up surveys suggest that they value incorporating scholarship into their careers more so than physicians from the comparison group. Discussion: The PC‐SDP seems to foster enthusiasm for scholarship by supporting residents' professional passions and facilitating successful projects. This may foster improved participation in scholarship in future clinical practice. Primary care physicians, including family physicians, lag behind hospital‐based physicians in research productivity